The Development of a Modified PDCA Management Model for Enhancing Curriculum Management Effectiveness in Sports Injury Rehabilitation Training for Non-Physical Education Students at Hubei Engineering University - Liu, Weichao; Jueajinda, Samith; Balsiri, Nitipatara (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to (1) identify key components and indicators of the modified PDCA management model for curriculum management; (2) analyze problems and needs in sports injury rehabilitation training; (3) design and validate a modified PDCA management model; and (4) examine the impact of improving curriculum management and practical performance. A mixed-methods design was implemented across four sequential phases. Phase 1 involved expert interviews with five specialists to identify the model’s core components and indicators. Phase 2 employed a survey of 390 students and 27 teachers/administrators to assess management problems and needs using a five-point Likert scale, with priority areas determined through the Modified Priority Needs Index (PNI). Phase 3 refined the model through expert validation with ten reviewers. Phase 4 evaluated its applicability and effectiveness using pre- and post-tests with 27 participants, supplemented by expert interviews. Data were analyzed using mean, standard deviation, modified PNI, and paired-sample t-tests, with all research instruments verified through Item–Objective Congruence and pilot testing. The findings revealed that (1) the modified PDCA model consists of four components and twelve indicators; (2) needs assessments indicated substantial gaps between current and expected performance, especially in optimizing teaching methods (PNI = 0.57) and improving content design (PNI = 0.54); (3) the final model integrated four components, twelve indicators, and thirty-six specific strategies; and (4) implementation produced a statistically significant improvement in curriculum management outcomes (t = 3.42, p < 0.05), and experts affirmed the model’s practicality and feasibility for curriculum enhancement in applied training contexts. The model provides a systematic and generalizable governance framework, offering guidance for institutional practices and policy-making.